Understanding morphology - Haspelmath, Martin, 1963-; Sims, Andrea D. (London : Hodder Education, 2010)
This introduction to morphology assumes no prior knowledge of linguistics and presents the field of morphology in an accessible way. Emphasis is put on presenting a range of morphological phenomena from a wide variety of languages.
Previous ed.: London : Arnold, 2002.
Includes bibliographical references (p. [301]-317) and index.
Keywords: Grammar, Comparative and general -- Morphology